Case report: Pulmonary hypertensive crisis leading to cardiac arrest during endoscopic evaluation in a 6-year-old boy with autism, severe malnutrition, and undiagnosed scurvy - Quinn, Laura A.; Gilley, Stephanie P.; Ta, Allison D.; Frank, Benjamin S.; Foley, Carolyn B.; Moore, Jaime M. (Frontiers in Pediatrics, 2022)
Pediatric gastroenterologists are often responsible for the evaluation of malnutrition in the setting of selective eating. Endoscopic evaluation for conditions including eosinophilic esophagitis and celiac disease can help to identify and treat mucosal disease contributing to food selectivity. However, undiagnosed micronutrient deficiencies can cause cardiovascular derangements that significantly increase a patient’s anesthetic risk. Vitamin C deficiency in particular, alone or in combination with severe malnutrition, is associated with a severe but reversible form of pulmonary arterial hypertension that, while life threatening in the acute phase, may significantly improve within days of starting ascorbic acid replacement therapy. Here we present a case of a 6-year-old boy with autism spectrum disorder (ASD), severe malnutrition, and undiagnosed chronic vitamin C deficiency who developed a pulmonary hypertensive crisis after induction of general anesthesia leading to cardiac arrest during endoscopic evaluation. While the association between food selectivity among youth with neurodevelopmental differences and vitamin C deficiency is well-described, and pulmonary hypertension is a recognized rare complication of scurvy, extant literature has not addressed next steps to improve patient outcomes. Using this case report as a foundation, we discuss specific patient populations to screen and treat for micronutrient deficiencies prior to anesthesia and propose a novel clinical algorithm for pre-anesthesia risk stratification and mitigation in patients specifically at risk for scurvy and associated pulmonary hypertension.